(untitled) (Revista Nacional de Odontología, 2014)
The term oral leukoplakia (ol) is strictly clinical and attributed to a predominantly white lesion with clinical and histological patterns of neoplastic characteristics commonly associated with a history of smoking. We therefore propose a provisional diagnosis of leukoplakia concluding with a biopsy to assess the histopathology for confirmation and determination of the degree of epithelial dysplasia, which leads to objectively determine and propose a therapy with the removal of triggering factors. Consideration of leukoplakia as a precancer- ous lesion comes mainly from follow-up studies that have demonstrated its malignant transformation. It is thus essential to know the molecular biology, which shows the forms and mechanisms of conversion of this precancerous entity to cancer. The objective of this review is to consider methods of diagnosis other than clinical ones, with the aim of evaluating the most important possible molecular markers of malignant potential of oral leukoplakia that have been studied and which play a fundamental role in the development of a true oral carcinoma.